Proceedings of the High-Energy Phenomena in Relativistic Outflows V meeting - Pellizza González, Leonardo Javier (2016)
The fifth meeting of the High-Energy Phenomena in Relativistic Outflows (HEPRO) series was successfully held in the city of La Plata, Argentina between 5 and 8 October 2015. It was organized by the Relativist Astrophysics Group And Radioastronomy based at the Argentine Institute for Radioastronomy (IAR-CONICET-CIC). The previous meetings of the series took place in Dublin (2007), Buenos Aires (2009), Barcelona (2011) and Heidelberg (2013). The meeting was attended by 79 participants from 16 countries in the Americas, Europe, Africa and Asia. There were 9 invited talks, 7 featured talks, 25 contributed talks, and 28 poster contributions. There were abundant and interesting discussions among the participants during the talks, which extended to the intervals of rest and social activities. The papers presented covered almost all fields of high-energy astrophysics: acceleration of particles, plasma and astrophysical flows (jets, winds, accretion discs), production of high-energy radiation, sources of non-thermal radiation (different types of binaries, active galactic nuclei, gamma ray bursts, pulsar nebulae, and more) and cosmic rays. The topics were approached from the point of view of the observations, theory and numerical simulations. This book contains a good sample of articles based on the lectures. The HEPRO V organization was sponsored by the National Council for Scientific and Technical Research (CONICET), the National Agency for the Promotion of Science and technology (ANPCyT), the Conmiittee for Scientific Research of the Province of Buenos Aires (CIG), the IAR, the Argentine Astronomical Society, the Faculty of Astronomy and Geophysics (FCAG-UNLP), the Argentine Physical Association (AFA), and the Abdus Salam Center for Theoretical Physics (ICTP). The event was declared of Legislative Interest by the Honorable Chamber of Senators of the Province of Buenos Aires, and of Municipal Interest by the Municipality of La Plata. We are grateful to all these organizations. We thank the Scientific Organizing Conmiittee for excellent advice that helped to shape the program, and the reviewers that read the papers offered in this volume. Special thanks go to the members of the LOG and those students who helped with the organization.